Soliton passively mode-locked pulses generation in thulium-holmium doped fiber laser (THDFL) with molybdenum oxide saturable absorber - Ahmad, Harith; Ismail, Norliana N.; Aidit, Siti Nabila; Yusoff, Norazriena; Ramli, Rizal; Abdul Kadir@Jaafar, Muhammad Zamzuri (Academic Press Inc., 2020)
This work proposed and demonstrated stable passive mode-locking in a thulium-holmium doped fiber laser (THDFL) using molybdenum oxide (MoOx) deposited onto a tapered fiber as a saturable absorber (SA). The SA was fabricated using the optical deposition technique for 2.0 µm region operation. The modulation depth, saturation intensity and non-saturable loss of MoOx SA were measured to be ~24.3%, ~0.01 MW/cm2 and ~75.7%, respectively. The threshold of the mode-locking operation was obtained at a pump power of 184.3 mW with a centre wavelength of 1937.1 nm and a 3-dB bandwidth of 4 nm. It has a high signal-to-noise ratio (SNR) of ~77 dB and produces a stable pulse with a repetition rate of 11.5 MHz and a pulse width of 1.64 ps